Six practical tips for practicing cyberhygiene in the middle of a global pandemic. Issue 2 (30th November 2020) - Peretti, Kimberly; Mushahwar, Amy; Knight, Jon
Abstract : Purpose: Discusses the long-term cybersecurity challenges businesses face as COVID-19 cases spike and remote work environments need to remain operational, scalable, and capable of flexing with cycles of virus resurgence. Design/Methodology/Approach: Discusses the target-rich environment cybercriminals have during this time, and steps businesses should take to secure their environments and raise employee awareness as more devices are being used remotely for company business and more company data is being sent, located, or stored outside the protections of the company infrastructure. Findings: The remote work environment is likely to be around for the foreseeable future and businesses need to ensure they are secured for long-term success. Practical implications: The authors offer information security and IT teams practical ways businesses can keep their systems secure and functioning: (1) Consider Basic Cyberhygiene; (2) Identify Security Blind Spots; (3) Review and Update Business Continuity, Disaster Recovery, and Incident Response Plans; (4) Remain Vigilant for Scams and Phishing Attacks; (5) Be Aware of Applicable Industry-Specific Guidelines; (6) Revisit Risk Exceptions. Originality/Value: Practical guidance from experienced data privacy and cybersecurity lawyers in response to COVD-19 for Information Security, IT, and business management teams.